Simira colorata (Rubiaceae), a new species from western Ecuador - Ståhl, Bertil; Persson, Claes (Phytotaxa, 2017)
Simira colorata from western Ecuador is described and illustrated. It is distinguished from other species of Simira by having rather small, glabrous leaves, with blades acute or obtuse at base, small non-calycophyllous, 4-merous flowers in rather large, pyramidal inflorescences, and small fruits. In vegetative features it resembles the Amazonian S. rubescens, which differs from S. colorata in its reproductive features. Although new to science, S. colorata, has been known and widely used in the Ecuadorian coast since the 18th century, and is nowadays endangered due to habitat loss.